Development of Video-Based K3 Learning Media as an Educational Strategy - Wahrini, Retyana (MultiTech Publisher, 2024)
The purpose of this study is to produce a video that can aid in the learning process, assess the viability of the film, and ascertain student reactions. This study employs the 4D (Four-D) development paradigm, which consists of the phases of define, design, develop, and disseminate. In order to collect replies to the Occupational Safety and Health (K3) learning film, students were also involved. The study's findings include: 1) interactive learning materials created through the research and development process, with the 4D (Four-D) development methodology utilized; 2) interactive learning materials in the form of instructional films for the Electronic Engineering Education FT UNM course on workplace safety and health, 3) Students' response as users of the learning video media was 95% with a very good category, while the study on the feasibility level of learning videos conducted by material experts obtained a feasibility level of 93% with a very feasible category and media experts obtained a feasibility level of 94% with a very feasible category. According to the findings of this study, students can benefit from using interactive learning materials in the form of instructional videos in the Occupational Safety and Health course in Electronic Engineering Education at FT UNM.